DNA methylation of the BRD2 promoter is associated with Juvenile Myoclonic Epilepsy in Caucasians - Pathak, Shilpa (Epilepsia, 2018)
OBJECTIVE: Juvenile Myoclonic Epilepsy (JME) is a common adolescent-onset genetic generalized epilepsy (GGE) syndrome. Multiple linkage and association studies have found that BRD2 influences the expression of JME. The BRD2-JME connection is further corroborated by our murine model: Brd2 haplo-insufficiency produces characteristics that typify the clinical hallmarks of JME. Neither we, nor several large-scale studies of JME, found JME-related BRD2 coding mutations. Therefore, we investigated non-coding BRD2 regions, seeking the origin of BRD2’s JME influence. BRD2’s promoter harbors a JME-associated SNP (rs3918149) and a CpG (C-phosphate-G dinucleotides) island (CpG76), making it a potential “hotspot” for JME-associated epigenetic variants. Methylating promoter CpG sites causes gene silencing, often resulting in reduced gene expression. We tested for differences in DNA methylation at CpG76 in three different subgroups: 1) JME patients vs. their unaffected family members, 2) JME vs. patients with other forms of GGE, and 3) Caucasian vs. non-Caucasian JME patients. METHODS: We used DNA pyrosequencing to analyze the methylation status of 10 BRD2 promoter CpG sites in lymphoblastoid cells from JME patients of Caucasian and non-Caucasian origin, unaffected family members, and also non-JME GGE patients. We also measured global methylation levels and DNA methyl transferase 1 (DNMT1) transcript expression in JME families by standard methods. RESULTS: CpG76 is highly methylated in JME patients compared to unaffected family members. In families with non-JME GGE, we found no relationship between promoter methylation and epilepsy. In non-Caucasian JME families, promoter methylation was mostly not associated with epilepsy. This makes the BRD2 promoter a JME-specific, ethnicity-specific, differentially methylated region. Global methylation was constant across groups. SIGNIFICANCE: BRD2 promoter methylation in JME, and the lack of methylation in unaffected relatives, in non-JME GGE patients, and in non-Caucasian JME, demonstrates that methylation specificity is a possible seizure susceptibility motif in JME risk and suggests JME therapeutics targeting BRD2.